Educational Values through Advertising. ONCE Campaigns on the Radio - García González, Aurora (2011)
Advertising transmits values that help forming a kind of society or bring to light the changes that occur in it. Our society is experiencing a rising level of awareness about the need to build a world with values, or human values. In the recent past, the ONCE advertising campaigns for radio enjoyed great reputation for quality of implementation and production. Some of the spots produced for these campaigns came to famous advertising festivals like SanSebastian, later called “The Sun”. What is interesting for this paper is the use of values in advertising discourse for persuasion. The detailed analysis of these campaigns can shed light on the potential of radio in the transmission of oral culture of the signifier.